Effect- and Performance-Based Auditory Feedback on Interpersonal Coordination - Hwang, Tong-Hun; Schmitz, Gerd; Klemmt, Kevin; Brinkop, Lukas; Ghai, Shashank; Stoica, Mircea; Maye, Alexander; Blume, Holger; Effenberg, Alfred O. (Frontiers in Psychology, 2018)
When two individuals interact in a collaborative task, such as carrying a sofa or a table, usually spatiotemporal coordination of individual motor behavior will emerge. In many cases, interpersonal coordination can arise independently of verbal communication, based on the observation of the partners’ movements or/and the object movement. In this study, we investigate how social coupling between two individuals can emerge in a collaborative task under different modes of perceptual information. A visual reference condition was compared with three new types of additional auditory information provided in real time: effect-based auditory feedback, performance-based auditory feedback, and combined effect/performance-based auditory feedback. A new paradigm has been developed in which the actions of both participants continuously result in a seamlessly merged effect on a tablet computer application. Here, participants were required to temporally synchronize their movements with a 90° phase delay and to precisely adjust the dynamics in order to keep a ball accurately rotating on a given circular trajectory on the tablet. Results demonstrate that interpersonal coordination in a joint task can be altered by different kinds of additional auditory information in various ways.